Being Human and Having Rights: Exploring Women's Education Under Sharia Law in Aceh - Ikhwan, M.; Zulfikar, T.; Ihsan Shadiqin , Sehat (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This article presents a literature review on the right to education under Sharia law in Aceh, a territory in Indonesia with special autonomy and formal application of Islamic law. The research methodology used the qualitative method with the literature review approach, encompassing data collection and analysis from diverse sources such as journals, books, reports, and websites to identify key issues, challenges, and opportunities faced by Acehnese women in accessing and utilizing education. The author also analyzes the role and impact of various actors, such as the government, non-governmental organizations, clerics, and communities, in shaping and influencing education policies and practices in Aceh. The article found that women's education in Aceh has made significant progress but also faces several obstacles, such as discrimination, violence, poverty, and a lack of participation. The authors recommend several steps to improve the quality and equity of women's education in Aceh, such as increasing budget allocation, involving women in decision-making processes, developing inclusive and relevant curricula, and strengthening cooperation between various stakeholders. Then also for further efforts be made to assess the empirical and normative impact of sharia law in Aceh on women's right to education and to develop inclusive, sensitive, and sustainable strategies to improve access, quality, and equity of women's education in Aceh.